Flat stone ceilings in the medieval Armenian architecture - Kazaryan, Armen (project baikal, 2024)
Flat stone ceilings were not typical for medieval architecture. Nevertheless, such ceilings had an exceptional development in Armenian architecture from the 11th to the 13th centuries. They were executed in different masonry techniques and with a decor resembling starry heavens. For the first time, an overview of flat ceilings in chronological development is given, as well as their role in the plans of the buildings is investigated. The analysis is aimed at identifying the reasons for their widespread use in memorial buildings. The initial samples were created in Ani back in the 11th century, and this trend later developed in the Armenian capital and monastic buildings.
Keywords: flat stone ceiling; Armenian architecture; Ani; memorial architecture; polychrome masonry; ancient tradition